ANALISIS PENGARUH HUTANG JANGKA PANJANG DAN MODAL KERJA BERSIH TERHADAP LABA PADA PT. JHI - Celsy Indrawati; Anik Yuliati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The research aims to analyze the effect of long-term debt and net working capital on profits. Long-term debt is national financial obligations for a period of one year or more, while net working capital is the difference between current assets and short-term debt and the company's ability to meet short-term obligations. With a qualitative method using data collection in the form of interviews, observation and documentation. Long-term debt has a significant impact on company profits and an increase in long-term debt can make a positive contribution to profits if used effectively for productive investment. Net working capital also has a significant influence on profits. This shows that there is good working capital management to increase the profitability of a company. This research concludes that long-term debt and current assets play an important role in obtaining company profits. Business owners are advised to make selections throughout the year to ensure efficient marketing management